2017
DOI: 10.1038/s41598-017-14319-7
|View full text |Cite|
|
Sign up to set email alerts
|

Method to Reduce Long-lived Fission Products by Nuclear Transmutations with Fast Spectrum Reactors

Abstract: Transmutation of long-lived fission products (LLFPs: 79Se, 93Zr, 99Tc, 107Pd, 129I, and 135Cs) into short-lived or non-radioactive nuclides by fast neutron spectrum reactors without isotope separation has been proposed as a solution to the problem of radioactive wastes disposal. Despite investigation of many methods, such transmutation remains technologically difficult. To establish an effective and efficient transmutation system, we propose a novel neutron moderator material, yttrium deuteride (YD2), to softe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…There are also long-lived fission products (LLFPs: 79 Se, 93 Zr, 99 Tc, 107 Pd, 129 I, and 135 Cs), which pose an additional nuclear waste challenge. It has been recently proposed to explore transmutation via fast neutron capture to shorter lived isotopes [182]. Further, the interplay between neutron capture and (n,2n) reactions may affect the transmutation efficiency [183].…”
Section: High Energy Neutron Induced Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also long-lived fission products (LLFPs: 79 Se, 93 Zr, 99 Tc, 107 Pd, 129 I, and 135 Cs), which pose an additional nuclear waste challenge. It has been recently proposed to explore transmutation via fast neutron capture to shorter lived isotopes [182]. Further, the interplay between neutron capture and (n,2n) reactions may affect the transmutation efficiency [183].…”
Section: High Energy Neutron Induced Measurementsmentioning
confidence: 99%
“…Symbols: (n,) direct measurements from Macklin et al, [185] and Nakamura et al, [186]. Blue line: Fast reactor relative neutron spectrum (arbitrary units) [182].…”
Section: High Energy Deuteron Induced Measurementsmentioning
confidence: 99%
“…For decades, elaborate schemes have been devised to attempt to separate such fission products and transmute them to stable isotopes, but none has been implemented. Even if ultimately successful, the cost and difficulty would be formidable (Chiba et al 2017). These fission products would also need to be geologically isolated in a deep underground repository for as long as some TRU isotopes.…”
Section: Consuming Nuclear Waste: the Realitymentioning
confidence: 99%
“…Regarding LLFP, a transmutation study has recently been conducted on 6 important nuclides ( 79 Se, 93 Zr, 99 Tc, 107 Pd, 129 I, and 135 Cs) from the viewpoint of reducing environmental influence. As a result, it was shown that the fast reactor can be used to transmute each of these 6 nuclides with a support ratio exceeding 1 using the YD2 moderator 28 . The significant reduction in the effective half-life was obtained by analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the support ratio (SR) was defined as the ratio of the amount of each nuclide transmuted by the fast breeder reactor to the amount of each nuclide (MA and LLFP) produced by the fast breeder reactor 28,30,31 .…”
Section: Introductionmentioning
confidence: 99%